2021
DOI: 10.20944/preprints202104.0409.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atypical Clinical Presentation of Laryngopharyngeal Reflux: A 5-year Case-Series

Abstract: Background: Laryngopharyngeal reflux (LPR) is a common disease in otolaryngology characterized by an inflammatory reaction of the mucosa of the upper aerodigestive tract caused by digestive refluxate enzymes. LPR has been identified as etiological or favoring factor of laryngeal, oral, sinonasal or otological diseases. In this case-series, we reported atypical clinical presentation of LPR in patients presenting in our clinic with reflux. Methods: A retrospective medical chart review of 351 patients with LPR tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…About one third of the analyzed patients suffered from LPR and GERD simultaneously [51]. As a consequence, saliva pepsin levels detection could be a useful instrument to investigate the potential involvement of LPR in primary BMS [52]. Another cause of discrepancy between older and current studies may lie in the focus of the former on low pH levels, but it has been well demonstrated that LPR as well as GERD are not exclusively acid in nature [53].…”
Section: Laringopharyngeal Refluxmentioning
confidence: 96%
“…About one third of the analyzed patients suffered from LPR and GERD simultaneously [51]. As a consequence, saliva pepsin levels detection could be a useful instrument to investigate the potential involvement of LPR in primary BMS [52]. Another cause of discrepancy between older and current studies may lie in the focus of the former on low pH levels, but it has been well demonstrated that LPR as well as GERD are not exclusively acid in nature [53].…”
Section: Laringopharyngeal Refluxmentioning
confidence: 96%